A Legal Study of Online Transportation Company Responsibility to Consumer Accident Safety - M. Fahrurozy; Redyanto Sidi; T. Riza Zarzani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the case of consumer rights violations, caution is needed in analyzing who should be responsible and how far the responsibility is imposed on the parties concerned. The responsibilities of business actors have been regulated in Law Number 08 of 1999 concerning consumer protection or UUPK, Articles 19 to 28, which include the principle of responsibility based on error (Liability Based On Fault Principle)and the principle of absolute liability ( Absolute Liability Principle) The formulation of the problem in this thesis is: What are the legal rules for transportation users?on line legislation, What is the role of the transportation line on the use of transportation line, What is the responsibility of the transportation company line to Gojek consumers in the event of an accident. While the research method used is library research (Library Research) in the form of Books, Laws, Government Regulations, and Field Research (Field Research) This research was carried out by conducting research at the Gojek Medan office which is located at Jalan Padang Golf complex CBD Polonia, Block AA No. 49-51 and Block BB No. 50, Medan Polonia, North Sumatra 20219, Obtaining data to support secondary data. Transportation companion line very big responsibility for consumer protection, because consumers play an important role in the use of services provided by transportation companies.